Gouverneur Morris and the American Revolution, - Mintz, Max M. (University of Oklahoma Press, 1970)
Report for Bachelor of Engineering (Naval Architecture)., ***CD-ROM held at loans desk***
Keywords: 1775-1783; New York (State); 1775-1783; United States; Biography; Legislators; Biography; United States; Foreign relations; History; Morris; Gouverneur; 1752-1816; Statesmen; Politics and government; Revolution; 1775-1783; dept.his; faculty_collection

Lyautey in Morocco: Protectorate Administration, 1912-1925 - Scham, Alan (University of California Press, 1970)
Keywords: Lyautey; Louis Hubert Gonzalve; 1854-1934; Morocco; Politics and government; dept.his; faculty_collection

An Incident in Elmina-Dutch Relations, The Gold Coast (Ghana), 1739-1740 - Feinberg, H. M. (African Historical Studies, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970Y060200006 tex.unique-id: [object Object]
Keywords: dept.his

Review of West African Trade and Coast Society: A Family Study - Feinberg, H. M. (African Historical Studies, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970Y060200027 tex.unique-id: [object Object]
Keywords: dept.his

2-Marriage Revolving-Mate Generation-Bridging Plan to Save Marriage - Tyler, RL (Humanist, 1970)
tex.unique-id: ISI:A1970Y053400012
Keywords: dept.his; ⛔ No DOI found